Do I fuck you or do you fuck me? Performance, pornotopia and aesthetic claim of violence in Baise-moi, by Virginie Despentes and Coralie Trinh Thi - Almeida, Gabriela Machado Ramos de (2022)
This paper presents an analysis of the film Baise-moi (2000), by Virginie Despentes and Coralie Trinh Thi, regarding it as a work capable of producing cracks in the ways of enunciating desire and certain affections commonly connected to “feminine” conventions. We propose a theoretical articulation between the formulations of Diana Taylor on performance, Paul B. Preciado on pornotopia, and Sam Bourcier on queer dissenting action to analyse three sequences of the feature film. We also use the theoretical and literary work of Despentes herself, which operates complementarily to the film and helps to perceive how Baise-moi produces an aesthetic claim of violence marked by traits such as exaggeration, graphic hyperviolence and explicit sex.